2021
DOI: 10.1007/s40200-020-00630-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot care course: a quasi-experimental study on E-learning versus interactive workshop

Abstract: Background Nurses, as multidisciplinary Diabetic Foot Care (DFC) team members, need to be trained in DF prevention and management. Regarding the increasing use of e-learning educational courses as the new learning strategy with potential benefits among health care providers, this study attempted to evaluate the educational effects of an e-learning course on DFC compared to that of an interactive workshop in the related knowledge attainment. Methods This was a quasi-experimental study compared two non-randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Nonetheless, in-person education may still result in higher knowledge acquisition than virtual learning. A study comparing e-learning with in-person education on diabetic foot care among nurses showed improvement in knowledge in both groups; however, participants who completed in-person workshops achieved higher knowledge scores than those attending virtually (31).…”
Section: Conclusion/discussionmentioning
confidence: 98%
“…Nonetheless, in-person education may still result in higher knowledge acquisition than virtual learning. A study comparing e-learning with in-person education on diabetic foot care among nurses showed improvement in knowledge in both groups; however, participants who completed in-person workshops achieved higher knowledge scores than those attending virtually (31).…”
Section: Conclusion/discussionmentioning
confidence: 98%
“…As per randomised controlled trials, educational interventions have been shown to be effective [ 31 , 32 , 33 ]. E-learning, when combined with a post session exam, can yield desired outcomes [ 36 ]. Although beyond the participants of this study, in more than 20% of DFU cases in a study, the PCP did not make the diagnosis, and the nurses played a significant role in the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Mas, no geral, a tecnologia foi bem avaliada pelos usuários, os quais relataram que a usaria novamente25 .Os vídeos educativos têm papel crucial na capacitação e atualização dos enfermeiros para direcionamento da consulta de enfermagem, a exemplo da demonstração prática dos testes para rastreamento da perda da sensibilidade protetora plantar em pessoas com DM. Os estudos consideraram que os vídeos educativos são efetivos, usuais, claros, adequados, podendo ser produzidos em diferentes idiomas, diminuindo a barreira linguística, até mesmo em linguagem de sinais22,28 .Outros estudos39,40 sobre a construção de vídeos educativos também demonstram um papel fundamental na educação em enfermagem, pois são bons recursos educativos para aprendizagem e desenvolvimento de habilidades que promovem mudanças significativas na vida dos estudantes. Os produtos tecnológicos tornaram-se uma parte essencial da prática assistencial, e surgem como ferramentas lúdicas altamente inovadoras, devido à sua versatilidade.…”
unclassified